2018
DOI: 10.3390/ijerph15122869
|View full text |Cite
|
Sign up to set email alerts
|

Job Burnout, Work-Family Conflict and Project Performance for Construction Professionals: The Moderating Role of Organizational Support

Abstract: Construction professionals are prone to work-family conflict and job burnout, which in turn can affect project performance during implementation of delivery. To cope with this, a questionnaire survey was undertaken with construction professionals in the Chinese construction industry and 373 valid responses were received. A theoretical model introducing organizational support as a moderating variable was developed and tested with structural equation modeling. The results showed that there is a positive correlat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
57
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(74 citation statements)
references
References 121 publications
8
57
0
3
Order By: Relevance
“…Work-family balance has been emphasized and proven to be associated with burnout. 17,35 Social support including family support has been investigated and validated to interfere with provider burnout. 36,37 Female physicians burdened with high risk pregnancies and miscarriages tend to experience higher burnout rates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Work-family balance has been emphasized and proven to be associated with burnout. 17,35 Social support including family support has been investigated and validated to interfere with provider burnout. 36,37 Female physicians burdened with high risk pregnancies and miscarriages tend to experience higher burnout rates.…”
Section: Discussionmentioning
confidence: 99%
“…Studies focused on wellness culture found that a positive culture increases provider performance, increases job security and satisfaction, and reduces provider burnout. 16,17 Each individual wellness culture domain has been reported previously in the literature. However, the findings are not consistent, and each study seemed to focus on different domains.…”
Section: Introductionmentioning
confidence: 99%
“…The contribution of the construction industry to China’s economy is also evident. China’s construction contractors are undertaking a large number of domestic and foreign construction projects, bringing huge occupational pressure and psychological burden to construction project managers (CPMs) [3]. Busy and committed construction project managers (CPMs) have to face common traditional challenges such as cost, time and quality, and they must also cope with ever-pressing safety and environmental issues [4].…”
Section: Introductionmentioning
confidence: 99%
“…Pengukuran dukungan organisasi menggunakan skala yang dikembangkan oleh Wu et al, (2018) dengan menggabungkan skala dari penelitian Eisenberger et al, (1986) terkait indikator dukungan supervisor, Hao et al, (2016) terkait identifikasi nilai yang dimiliki oleh karyawan terhadap dukungan organisasi dan Yang et al, (2018) terkait perhatian yang diberikan karyawan terhadap organisasi. Total aitem dalam skala ini berjumlah 6 butir dengan nilai alpha cronbach 0,94.…”
Section: Dukungan Organisasiunclassified